2010
DOI: 10.1108/08876041011060440
|View full text |Cite
|
Sign up to set email alerts
|

Service quality, trust, commitment and service differentiation in business relationships

Abstract: PurposeWhile service quality, trust and commitment are frequently cited as critical to achieving important firm outcomes, the role of service differentiation in this framework is largely unknown. Yet, differentiation is important because a firm's distinctiveness is linked to client‐perceived value, competitive advantage, and a target market focus. Thus, the purpose of this study is to examine the role of service differentiation in business‐to‐business relationships.Design/methodology/approachHypotheses were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 94 publications
5
118
2
4
Order By: Relevance
“…Recent findings confirm the common sense expectation that perceived service quality is a key contributor to satisfaction with the service provider (Rauyruen & Miller, 2007;Molinari, Abratt & Dion, 2008;Chenet et al, 2010). Given the significant amount of research on the links between service quality and satisfaction in both offline (Williams, Khan, Ashill & Naumann., 2011) and online contexts (Rafiq et al, 2012), it is suggested that the same relationship will operate in the B2B domain:…”
Section: H5: There Is a Positive Relationship Between Technology Readsupporting
confidence: 62%
See 1 more Smart Citation
“…Recent findings confirm the common sense expectation that perceived service quality is a key contributor to satisfaction with the service provider (Rauyruen & Miller, 2007;Molinari, Abratt & Dion, 2008;Chenet et al, 2010). Given the significant amount of research on the links between service quality and satisfaction in both offline (Williams, Khan, Ashill & Naumann., 2011) and online contexts (Rafiq et al, 2012), it is suggested that the same relationship will operate in the B2B domain:…”
Section: H5: There Is a Positive Relationship Between Technology Readsupporting
confidence: 62%
“…A high level of service quality is positively associated with satisfaction, and loyalty, in both offline (Fullerton, 2005;Rauyruen & Miller, 2007;Williams, Khan, Ashill & Naumann, 2011) and online contexts (Rafiq, Lu & Fulford, 2012), and can give service providers competitive advantage (Chenet, Dagger & O'Sullivan, 2010). Gounaris (2005) suggested that there are four determinants of service quality in a B2B environment: Potential, Hard Process, Soft Process and Output Quality.…”
Section: Service Qualitymentioning
confidence: 99%
“…Since the strength of ingredient brands constitutes a quality signal (Rao & Ruekert, 1994), in line with signaling theory (Kirmani & Rao, 2000;Nelson, 1974), in which brand quality influences customer trust (Caceres & Paparoidamis, 2007;Chenet, Dagger, & O'Sullivan, 2010), we also propose the existence of a direct relationship between brand strength and brand trust and offer the following hypotheses:…”
Section: Ingredient Brand Strengthmentioning
confidence: 83%
“…61 If customers become less trusting of a fi rm ' s behaviour, over repeated transactions, they will spread negative word of mouth and thereby reduce the fi rm ' s value-creation pie if they hold beliefs about a fi rm ' s misbehaviour. 56,62 If a fi rm does not consider these issues, CRM activities will potentially cross the line in terms of what the consumers consider fair. As a result, this may decrease trust in fi rm activities and cause dissatisfaction and loss of potential key advantages.…”
Section: Exploitation Of Consumer Privacy and Valuementioning
confidence: 99%
“…In the past, trust has been defi ned as a willingness of an exchange party to be vulnerable to the actions of another party in whom one has confi dence . 63 (For more about the trust concept, see Morgan and Hunt, 17 Chenet et al , 62 Bart et al , 64 and Fang et al 65 ).…”
Section: Exploitation Of Consumer Privacy and Valuementioning
confidence: 99%